Philippine Economic Update, December 2012 : Accelerating Reforms to Sustain Growth - World Bank Group (World Bank, Manila, 2017)
The Philippine economy has emerged as one of the fastest growing economies in East Asia, with growth accelerating to 7.1 percent in the third quarter. The acceleration of domestic demand since the first quarter of 2012 reflects the country's strong macroeconomic fundamentals, stronger government finances, and high confidence in the Aquino government's commitment to reform. Sound macroeconomic fundamentals, as seen in low inflation, and large current account surpluses and foreign exchange reserves, have continued to shield the economy from external headwinds, while a more diversified export basket allowed total exports to grow, despite the decline in electronics exports. Overall, the economy is expected to expand by over six percent this year, up from 3.9 percent last year. However, more structural reforms are needed to create more and better jobs, as the overall labor market outcome has been less responsive to the higher economic growth. The economy needs to shift from consumption towards investment, both public and private. The special focus sections of this update demonstrate that the implementation of such reforms can have high payoffs in terms of jobs and inclusive growth. Finally, by scaling-up and broadening several open government/open data initiatives in the country, the strengthening of inclusive institutions would be greatly enhanced, in line with the core principles of this government.